Supply as a factor in the destabilization of the oil market. (December 2020) - Filimonova, I.V.; Kozhevin, V.D.; Nemov, V.Y.; Komarova, A.V.; Mishenin, M.V.
Abstract: The article deals with the fundamental and conjuncture factors of the oil market equilibrium. The purpose of the study is to identify new economic indicators that affect the global pricing model in the oil market, and determine the effectiveness of the existing cartel agreement. The structure of net energy consumption, as well as features of demand for energy resources by regions of the world, is presented in the article. The study provides a comprehensive statistical analysis of the dynamics of changes in oil prices and production indicators of the largest oil producing countries in the world. The analysis highlights the factors of the oil market stabilization from the demand and supply side: production, technological and price factors. Relative indicators, such as the level of technology development and drilling efficiency in the respective segments, were found to have the greatest impact on the stability of energy prices, and long-term price stabilization is possible only if the US oil industry participates in OPEC+ agreement.